Spiritual intelligence: narrowing the gap between the ethical and non-ethical values of public sector employees / Rozaiha Abd Majid, Nafsiah Mohamed and Zanariah Mahmud - Abd Majid, Rozaiha; Mohamed, Nafsiah; Mahmud, Zanariah (Universiti Teknologi MARA Cawangan Selangor, 2010)
This paper highlights the possibility that having the knowledge in spiritual intelligence could deter and ultimately eliminate fraud in the Public Sector in Malaysia. This is due to the fact that having a good internal control does not guarantee that the employees would not conduct fraud. A study conducted in a local authority proved that a good internal control system may not be the effective answer to prevent fraud from occurring. It is recommended that knowledge and awareness in spiritual intelligence could improve the ethical values among employees.